2015
DOI: 10.1039/c4nr05656f
|View full text |Cite
|
Sign up to set email alerts
|

Giant piezoresistivity in aligned carbon nanotube nanocomposite: account for nanotube structural distortion at crossed tunnel junctions

Abstract: High piezoresistivity is critical for multifunctional carbon nanotube polymer composites with sensing capability. By developing a new percolation network model, this work reveals theoretically that a giant piezoresistivity in the composites can be potentially achieved by controlled nanotube alignment resulting from field based alignment techniques. The tube-tube and/or tube-matrix interaction in conjunction with the aligned carbon nanotube networks are fully considered in the newly proposed model. The structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…In this context, CNT doped nanocomposites have a great potential and applicability. This is explained by the intrinsic piezoresistivity of CNTs [13,14], the contact conductive mechanism between CNTs and the tunneling effect that takes place between adjacent nanotubes. The combination of these factors leads to an enhanced strain sensitivity, much higher than those achieved for conventional metallic gauges [15][16][17][18][19].There are several studies of materials manufactured by 3D printing with CNTs as conductive fillers.…”
mentioning
confidence: 99%
“…In this context, CNT doped nanocomposites have a great potential and applicability. This is explained by the intrinsic piezoresistivity of CNTs [13,14], the contact conductive mechanism between CNTs and the tunneling effect that takes place between adjacent nanotubes. The combination of these factors leads to an enhanced strain sensitivity, much higher than those achieved for conventional metallic gauges [15][16][17][18][19].There are several studies of materials manufactured by 3D printing with CNTs as conductive fillers.…”
mentioning
confidence: 99%
“…Finally, Gong and Zhu revealed that a giant piezoresistivity may be achieved by controlling the cnt alignment in cnt/ polymer nanocomposites [73]. Figure 14(a) and (b) shows that the highest piezoresistive effect may be achieved in both directions parallel and perpendicular to the alignment by controlling the maximum cnt alignment angle between 10° and 20°.…”
Section: Figure 13mentioning
confidence: 96%
“…Until now, only a limited number of studies [44], [56], [61]- [73] have explored the piezoresistive behavior and the associated mechanisms of cnt/polymer composites quantitatively. Analytical studies [63], [64], [68], usually based on the Simmons tunneling effect at the cnt junctions [24], have tried to explain the mechanism of piezoresistivity in cnt/polymer nanocomposites.…”
Section: R R0 Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, several investigations have highlighted the existence of a giant piezoresistive effect (the electron conductivity can change by 9 orders of magnitude) in composite materials constituted by a silicone matrix filled by conductive microparticles at a volume fraction around percolation threshold [8][9][10].…”
Section: Introductionmentioning
confidence: 99%